Genuss als Politikum. Kaffeekonsum in beiden deutschen Staaten - Sigmund, Monika 1965- (Studien zur Zeitgeschichte, 2015)
In East and West Germany, coffee took on great symbolic value as an indicator of prosperity, both for the individual and society. In her comparative and richly illustrated presentation, Monika Sigmund reveals the status and emotional valence that were associated with drinking a cup of coffee. In both Germanys, coffee consumption was far more than just a private act